PH- and glutathione-responsive release of curcumin from mesoporous silica nanoparticles coated using tannic acid–Fe(iii) complex. Issue 110 (22nd October 2015) - Kim, Sanghoon; Philippot, Stéphanie; Fontanay, Stéphane; Duval, Raphaël E.; Lamouroux, Emmanuel; Canilho, Nadia; Pasc, Andreea
Abstract : A novel pH- and glutathione-responsive drug delivery system has been developed by deposition of tannic acid (TA)–Fe(iii ) complex on the surface of mesoporous silica nanoparticles (MSN). Abstract : A novel pH- and glutathione-responsive drug delivery system has been developed by deposition of tannic acid (TA)–Fe(iii ) complex on the surface of mesoporous silica nanoparticles (MSN). The coating was easily accomplished within 30 seconds by successive addition of iron chloride (FeCl3 ) and tannic acid in aqueous dispersion of MSN ( e.g. MCM-41). A hydrophobic model drug, curcumin, showed sustainable drug release under physiological condition (pH 7.4), while a rapid curcumin release was triggered by lowering the pH to 6.0 or 4.5. Moreover, curcumin release could be controlled by adjusting the glutathione level, which accelerate the decomposition of TA–Fe(iii ) complex by competitive liganding. Therefore, these results would allow developing novel and simple pH- and glutathione-responsive drug delivery systems with potential applications such as in biomedicine.